Industrial water tube boiler design : formulas in practice - Mousapoor, Mehran (De Gruyter, 2021)
This book consists of steps for the thermal & mechanical design of d-type watertube boilers. It provides the reader with guidance for burner, fan size, and capacity selection, furnace thermal and dimensional design, super heater primary thermal and mechanical design, and boiler bank and economizer design. Calculations of the methods and efﬁciency are also described.
Keywords: Steam-boilers, Water-tube -- Design and construction.; elektronické knihy; electronic books